Effect of Financial Performance on Stock Prices of Manufacturing Companies in Malaysia; Moderating Role of Sustainability Reporting - Maryam Yousefinejad; Aza Azlina Md Kassim; Tahani Ali Hakami; Jaizah Othman; Poovarashan Manivannan (International Business and Accounting Research Journal, 2022)
The purpose of this study is to examine the relationship between financial performance (FP) and stock prices (SP) of Malaysian manufacturing companies. This study also examines the effect of sustainability reporting on the relationship between FP And SP. If the information reported in financial statements were useful, this information would affect investors' reactions. Investors' reactions are reflected in their transactions in the capital market. Desirable reactions to information are shown by an increase in demand for a company's stock, which leads to an increase in its stock price. Undesirable reactions to information, on the other hand, result in a decrease in demand for a company's stock, leading to a decrease in the stock price. Therefore, capital markets research is often used to examine investor reactions to corporate information disclosure and to evaluate the relevance of alternative accounting and disclosure decisions to investors. Based on the efficient market hypothesis (EMH), this study hypothesized that financial performance has a positive effect on the stock prices of manufacturing companies in Malaysia. Financial performance is critical but not sufficient for corporate survival. Companies can achieve sustainable performance just to meet mutual expectations of doing business. Therefore, based on the institutional theory, this study hypothesizes that a sustainability reporting strengthens the relationship between financial performance and stock price. The hypotheses were empirically tested using a sample of 74 Malaysian manufacturing companies from 2018 to 2019 using an Ordinary Least Square (OLS). The results of this study indicate a positive and significant relationship between FP and SP. In addition, this study found that sustainability reporting strengths the effect of FP on stock prices enhancement.